Head circumferences of children born to HIV-infected and HIV-uninfected mothers in Zimbabwe during the preantiretroviral therapy era. (24th September 2016) - Evans, Ceri; Chasekwa, Bernard; Ntozini, Robert; Humphrey, Jean H.; Prendergast, Andrew J.
Abstract : Objectives: To describe the head growth of children according to maternal and child HIV infection status. Design: Longitudinal analysis of head circumference data from 13 647 children followed from birth in the ZVITAMBO trial, undertaken in Harare, Zimbabwe, between 1997 and 2001, prior to availability of antiretroviral therapy (ART) or cotrimoxazole prophylaxis. Methods: Head circumference was measured at birth, then at regular intervals through 24 months of age. Mean head circumference-for-age Z -scores (HCZ) and prevalence of microcephaly (HCZ < −2) were compared between HIV-unexposed children, HIV-exposed uninfected (HEU) children and children infected with HIV in utero (IU), intrapartum (IP) and postnatally (PN). Results: Children infected with HIV in utero had head growth restriction at birth. Head circumference Z -scores remained low throughout follow-up in IP children, whereas they progressively declined in IU children. During the second year of life, HCZ in the PN group declined, reaching a similar mean as IP-infected children by 21 months of age. Microcephaly was more common among IU and IP children than HIV-uninfected children through 24 months. HEU children had significantly lower head circumferences than HIV-unexposed children through 12 months. Conclusion: HIV-infected children had lower head circumferences and more microcephaly than HIV-uninfected children. Timing of HIV acquisition; influenced HCZ, with those infected before birth having particularly poor head growth. HEU children had poorer head growth until 12 months of age. Correlations between head growth and neurodevelopment in the context of maternal/infant HIV infection, and further studies from the current ART era, will help determine the predictive value of routine head circumference measurement.